Impacts of competitive strategy and ownership structure on internet finance platforms in China - Tian, Zhongkai (2020)
Internet finance refers to a business method that utilizes the internet and information communication technologies to accomplish financial activities. Internet finance has experienced a phenomenon growth in China’s financial market, providing investment choices for individual investors, and serving as the financing channels for the SMEs. This research aims to fill the gap by identifying and empirically examining the competitive strategy factors that are related to firm performance of internet finance platforms in China. The research also seeks to examine how ownership structure influenced the relationship between competitive strategies and firm performance of internet finance platforms in China. Based on the competitive strategy theory, institutional theory, and agency theory, this research proposes a theoretical framework that examines the factors of competitive strategies that influenced firm performance and the moderation effect of ownership structure. Data were collected from various official websites and third-party database. A total of 500 internet finance platforms and their operations information were collected over a period of 13 months, from June 2017 to June 2018. Structural equation modelling (SEM) was deployed for testing the hypotheses. The results indicated that competitive strategies were related to firm performance in the internet finance platforms in China. Ownership structure was found to moderate the relationship between competitive strategies and firm performance of internet finance platforms in China. The results drawn from this study showed that the factors LP (loan periods), IR (interest rate), TT (total transaction), and NI (number of investors) could be identified by individual investors and these can be used when making investing decisions so as to avoid potential risks. This research provides insights into the operational information of internet finance platforms which can be gathered from third-party websites. This empirical research disclosed information on firm performance based on the internet finance platforms. These can be potentially utilized by individual investors to make investment decisions. This research could also help internet finance platforms participators to enhance their performance, thereby contributing to the healthy development of internet finances in China.